(untitled) (Integral Research, 2025)
Chhotu Ram was an important leader of the Indian freedom struggle, whose contribution was especially for the rights of farmers and their rights. His life was dedicated to the struggle against British rule and reforms in Indian society. Chhotu Ram was born in 1881 and belonged to a farmer family. From the beginning of his education and social service, he understood the problems of farmers and tried to find solutions to them. He made many reform schemes for farmers and raised his voice for their rights. Chhotu Ram’s contribution to the freedom struggle was mainly in the form of farmer movement and social reforms. He believed that independence should not be only political, but also in social and economic terms. He fought against British rule along with Congress and other agitators. He was of the view that true independence in India is not possible without the welfare of farmers and improving their condition. Chhotu Ram’s contribution is still considered important in Indian politics and society, and his ideology holds a permanent place in the history of the Indian freedom struggle.